2015
DOI: 10.1021/jp512839q
|View full text |Cite
|
Sign up to set email alerts
|

Live Cell Plasma Membranes Do Not Exhibit a Miscibility Phase Transition over a Wide Range of Temperatures

Abstract: Lipid:cholesterol mixtures derived from cell membranes, as well as their synthetic reconstitutions, exhibit well defined miscibility phase transitions and critical phenomena near physiological temperatures. This suggests that lipid:cholesterol-mediated phase separation plays a role in the organization of live cell membranes. However, macroscopic lipid phase separation is not generally observed in cell membranes and the degree to which properties of isolated lipid mixtures are preserved in the cell membrane rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 69 publications
1
46
0
Order By: Relevance
“…2C and F). This suggests that the plasma membrane domains containing these proteins do not undergo a miscibility phase transition across the temperature range we studied, in agreement with a recent FCS study in live cells [15]. …”
Section: Discussionsupporting
confidence: 92%
“…2C and F). This suggests that the plasma membrane domains containing these proteins do not undergo a miscibility phase transition across the temperature range we studied, in agreement with a recent FCS study in live cells [15]. …”
Section: Discussionsupporting
confidence: 92%
“…Similarly, numerous reports suggest that raft and non-raft membrane peptides exhibit qualitatively similar confinement behaviors 130, 137, 138 . Another study showed that diffusion varied smoothly with temperature for a range of different probe molecules, concluding that there was no evidence for an in situ phase transition in live cells 139 . Yet another found that probe localization and diffusion was not affected by the presence of macroscopic raft-like domains generated by binding raft proteins to a patterned surface 140 .…”
Section: Detecting Rafts Through Diffusionmentioning
confidence: 99%
“…To specifically further assess how exogenous treatments affect the plasma membrane, we generated giant plasma membrane vesicles (GPMVs) which retain most of the full diversity of native membrane components, but lack cytoskeletal attachment[161]. This type of reductionist approach allows us to probe specific questions regarding the interaction between diet-derived bioactives and lipid membranes without the complication of compensatory mechanisms imparted by the live cell such as membrane tension[162] and cytoskeletal remodeling[108]. GPMVs were isolated from YAMC-HRasG12V cells pre-labeled with Di4 and incubated with varying doses of (+)-catechin and procyanidin B2 (Figure 2C&D).…”
Section: Introductionmentioning
confidence: 99%